Pengaruh Corporate Governance terhadap Inovasi dan Kinerja Perusahaan: Studi pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang terdaftar di Bursa Efek Indonesia periode 2018-2020 - Warda, Zahrotul; Hanifah, Salma (Journal of Economic, Management and Entrepreneurship, 2023)
The purpose of this study was to determine and measure the influence of corporate governance on innovation and company performance. This research was conducted on Manufacturing Companies (consumer goods industry sector) listed on the Indonesia Stock Exchange (IDX) for the period 2018 - 2020. The selection of research samples using purposive sampling was 14 companies. The data analysis used is WarPLS 7.0 (Partial Least Square) software. The sampling method used is the purposive sampling technique. The results of the study show that (1) the Corporate Governance variable has a significant effect on innovation. (2) Corporate Governance variable has no significant effect on Company Performance. (3) The innovation variable has a significant effect on the company's performance. (4) corporate governance variables have a significant effect on company performance variables through innovation.